Wings - Saunders, John Monk 1897-1940; Zamecnik, J. S. 1872-1953
"Two young men, one rich, one middle class, are in love with the same woman, but must leave her behind when they become fighter pilots in World War I." [imdb.com]
Orig: USA 1927